Morphological and Molecular Discrimination of Fasciola Species Isolated From Domestic Ruminants of Urmia City, Iran - Mohammad Yakhchali; Reza Malekzadeh-Viayeh; Abbas Imani-Baran; Karim Mardani (Iranian Journal of Parasitology, 2015)
Background: The trematodes of the genus Fasciola (the liver flukes) are among the well-known instances of food-borne parasites worldwide. Differentiation of Fasciola species is important because of their different transmission and epidemio-logical characteristics. The current study was undertaken to discriminate Fasciola species in the domestic ruminants of Urmia city, Iran.